Business Development Frameworks for Establishing Innovative Born-Global Firms in Nigeria and Sub-Sahara Africa - Ezepue, Patrick Oseloka; Ochinanwata, Nonso (Journal of Advances in Management Sciences & Information Systems, 2017)
This conceptual paper explores different approaches for establishing born-global firms (BGFs) in developed and developing countries, with a special focus on Nigeria and Sub-Sahara Africa. It reviews the key constructs and frameworks that underpin new business development in born-global firms. Examples of these constructs are business development, dynamic capabilities, innovation, collaboration, entrepreneurship, and organisational learning. The research is important because of the relative lack of BGFs (Google, Amazon, Alibaba, and Facebook, for example) in Sub-Sahara Africa, compared to other parts of the world. Moreover, the frameworks for BGF new business development can be applied in subtly different ways in developed and developing country contexts. For example, BGFs in developed countries focus on niche products and services with breakthrough innovation, whilst those in developing countries, because of limited resources and capabilities, focus on underserved and mass markets, which do not require high level resources and capabilities. Realistic hypothetical examples of BGFs which directly underpin Nigerian and Sub-Sahara African higher education and economic development are used to illustrate the BGF business development constructs.